PERMASALAHAN ORANG TUA DALAM MENDIDIK REMAJA DI AIR DINGIN KELURAHAN BALAI GADANG KECAMATAN KOTO TANGAH PADANG - Zilfiyeni, Chintia - (Bimbingan dan Konseling, 2014)
This research is parent who are experiencing problem in educating teenagers. The focus of the research: 1) The moral aspect and 2) The psychological aspect. Qualitative research, the informants are: parents teenagers (father and mother) and teenagers sister. The instruments is interview and documentation in the form attached photos, the technique of data through data reduction, data presentation and conclusion. The result of this research is parent have problems in educating teenagers: 1) The moral aspect is the parents who have not been able to steer teenagers well than peers attitudes teenagers parents make it difficult to steer teenagers that teenagers attitude could change into a better direction and 2) The psychological aspects is the parents who have not been able to control emotions of teenagers and teenagers who are able to alleviate directives given to teenagers parents so that teenagers ignored the directives given to teenagers parent